2010
DOI: 10.1186/1751-0147-52-26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical changes in 53 Swedish dogs bitten by the European adder - Vipera berus

Abstract: BackgroundEvery year many dogs in Sweden are bitten by Vipera berus, the only venomous viper in Sweden. This prospective study investigated clinical signs, some biochemical parameters, treatment, and progress of disease after snakebite in 53 dogs. Effects of treatment with and without glucocorticoids were evaluated.MethodsAll fifty-three dogs bitten by Vipera berus were examined the same day the dog was bitten and the next day. Two more examinations during 23 days post snake bite were included. Creatinine, cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
2
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 14 publications
9
44
2
11
Order By: Relevance
“…However, in the United States envenomation has been recently estimated to affect 150,000 dogs and cats per year (Gilliam and Brunker, 2011) and in the United Kingdom, 0.7% of the calls to Veterinary Poisonous Information Services were reported to be related to snake envenomation events (Sutton et al, 2011). Mortality of dogs secondary to snake envenomation in different parts of the world has been reported to be from 1 -5% (Lervik et al, 2010;Gilliam and Brunker, 2011;Sutton et al, 2011) and as high as 30% (Gilliam and Brunker, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the United States envenomation has been recently estimated to affect 150,000 dogs and cats per year (Gilliam and Brunker, 2011) and in the United Kingdom, 0.7% of the calls to Veterinary Poisonous Information Services were reported to be related to snake envenomation events (Sutton et al, 2011). Mortality of dogs secondary to snake envenomation in different parts of the world has been reported to be from 1 -5% (Lervik et al, 2010;Gilliam and Brunker, 2011;Sutton et al, 2011) and as high as 30% (Gilliam and Brunker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly observed clinical manifestations of renal abnormalities after snake envenomation in humans and dogs are acute kidney injury (AKI), proteinuria and hematuria (Sitprija, 2006;Kanjanabuch and Sitprija, 2008;Goddard et al, 2011) The majority of studies and reports of snake envenomation in dogs have focused on routine serum analyses and only to some extent on urinalysis (Heller et al, 2007;Lervik et al, 2010;Gilliam and Brunker, 2011;Sutton et al, 2011). Nevertheless, these parameters are nonspecific and insensitive as they are only altered at the point when about 50 -75% of renal function is already lost (Finco, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The only significant change regarding the administration of glucocorticoid drugs or antihistamines in the dogs was a higher leukocyte count following therapy . Another recent canine study of 53 dogs reported no obvious positive or negative effects with antiinflammatory or immunosuppressive doses of oral or injectable prednisone administration (0.1–2 mg/kg for 1–5 days) after natural envenomation by the European adder ( Vipera berus ) …”
Section: Treatmentmentioning
confidence: 99%
“…In another study, 12 clinical and serum biochemical changes were evaluated in dogs that had been bitten by European adders. For 23 of 28 (82%) dogs, the serum creatinine concentration on the day a dog was bitten was higher than the concentration on the next day.…”
Section: Comparing 2 or More Distributions Of Repeated Measurementsmentioning
confidence: 99%